2023
DOI: 10.1029/2022jd037824
|View full text |Cite
|
Sign up to set email alerts
|

QBO/Solar Influences on the Tropical Madden‐Julian Oscillation: A Mechanism Based on Extratropical Wave Forcing in Late Fall and Early Winter

Abstract: The tropical Madden-Julian oscillation (MJO) is an eastward propagating, convectively coupled, tropical wave that produces the strongest of the intraseasonal climate oscillations (e.g., Adames & Kim, 2016;Sobel & Maloney, 2012). It generates a Rossby wave train that can be associated with high-impact weather events at northern midlatitudes (e.g., Matthews et al., 2004;Zhang, 2013).Recent research has found that the stratospheric quasi-biennial oscillation (QBO) (e.g., Baldwin et al., 2001) modulates the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…(2021). For the pre‐satellite (1959–1973) period, the same package was applied to the ERA5 OLR data (see, e.g., Hood & Hoopes, 2023; their Section 2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2021). For the pre‐satellite (1959–1973) period, the same package was applied to the ERA5 OLR data (see, e.g., Hood & Hoopes, 2023; their Section 2).…”
Section: Methodsmentioning
confidence: 99%
“…Positive feedbacks from below including cloud‐radiative feedbacks (Sakaeda et al., 2020; Son et al., 2017) and QBO influences on the MJO‐induced cold cap anomaly ahead of MJO convection (Hendon & Abhik, 2018; Kodera et al., 2023; Lim & Son, 2020) are likely necessary to explain the full amplitude of the observed modulation. Several studies have found that the QBO‐MJO connection has strengthened significantly since the early 1980s, coinciding with long‐term decreases in tropical static stability (Hood & Hoopes, 2023; Klotzbach et al., 2019; Sakaeda et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way that the QBO can affect temperature and static stability in the tropical lower stratosphere is via QBO influences on extratropical wave forcing of the stratospheric residual meridional circulation, the “Brewer‐Dobson” circulation, or BDC (Hood, Trencham, & Galarneau, 2023; hereafter HTG23). Extratropical wave forcing in the Northern Hemisphere is mainly responsible for producing the climatological minimum in tropical lower stratospheric temperature that occurs near the middle of boreal winter (e.g., Randel et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Holton‐Tan effect changes sign in late boreal winter with stronger wave forcing on average during QBOW than during QBOE (Lu et al., 2020, and references therein). QBOE‐induced cooling anomalies in the equatorial lower stratosphere are noticeably larger in boreal winter than in other seasons and are complemented by warming anomalies at high latitudes, implying an important role of extratropical wave forcing in producing the observed static stability reductions in QBOE (see, e.g., Figure 1 of HTG23). The Holton‐Tan effect is not simulated well in current coupled climate models (e.g., Elsbury et al., 2021), due in part to lack of a sufficiently strong and continuous easterly QBO phase in most models.…”
Section: Introductionmentioning
confidence: 99%